2016
DOI: 10.3390/polym8090333
|View full text |Cite
|
Sign up to set email alerts
|

Dilute Semiflexible Polymers with Attraction: Collapse, Folding and Aggregation

Abstract: Abstract:We review the current state on the thermodynamic behavior and structural phases of self-and mutually-attractive dilute semiflexible polymers that undergo temperature-driven transitions. In extreme dilution, polymers may be considered isolated, and this single polymer undergoes a collapse or folding transition depending on the internal structure. This may go as far as to stable knot phases. Adding polymers results in aggregation, where structural motifs again depend on the internal structure. We discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 138 publications
(195 reference statements)
4
43
0
Order By: Relevance
“…Hairpins and toroids exist at high stiffness, but they are no longer the ground state, which is a knotted structure, ideally the trefoil knot as for L=0.51 and N=40. The knotted structures in general have moved to the high stiffness region (they occur for L0.6) and are not found in the intermediate stiffness region, like in [22,23], where the high stiffness region is dominated by hairpins and folded chains. This comparison thus confirms our claim from the introduction: not all stiffnesses are created equal [7], and this is true even for models exhibiting the persistent mechanism of flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hairpins and toroids exist at high stiffness, but they are no longer the ground state, which is a knotted structure, ideally the trefoil knot as for L=0.51 and N=40. The knotted structures in general have moved to the high stiffness region (they occur for L0.6) and are not found in the intermediate stiffness region, like in [22,23], where the high stiffness region is dominated by hairpins and folded chains. This comparison thus confirms our claim from the introduction: not all stiffnesses are created equal [7], and this is true even for models exhibiting the persistent mechanism of flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies were performed for chains of lengths N=40256, a Wang–Landau Monte Carlo [19,20] study of such semi-flexible bead-spring chains in the continuum, performed for chains of length N=1355 [21] later confirmed the occurrence of these morphologies. Recently a similar model was studied by multi-canonical simulations [22,23], and it was shown that ground states at different stiffness can also be characterized by their knottedness (here, knots are defined by joining the two ends of the chain by an additional long bond).…”
Section: Introductionmentioning
confidence: 99%
“…Bonds are modelled between neighbouring monomers by the FENE potential V FENE ( r )=−( KR 2 /2)ln[1−( r − r 0 ) 2 / R 2 ] with K =40, R =0.3 and r 0 =0.7. Non-bonded monomers interact with the same Lennard-Jones potential as above but with σ = r 0 2 −1/6 such that r min = r 0 18 19 20 . The total number of monomers is 13 N , which yields 3 × 13 N total momentum degrees of freedom in equation (5) and successive relations.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, we consider a setup at fixed density with varying temperature—an intuitive approach from a condensed matter perspective. We focus on aggregation of polymers in a dilute setup 18 19 20 guided by the canonical case of droplet formation in a particle gas. For the canonical case, we analyse a two-dimensional free-energy landscape and identify the energy as a suitable reaction coordinate.…”
mentioning
confidence: 99%
“…The sum of the FENE and the non-bonded potential provides a total interaction between two connected monomers showing a deep minimum at r ∼ 0.95, which guarantees uncrossability and prevents violation of the topological constraints. In the case of the semiflexible linear chains the bending stiffness was implemented through the worm-like model [29,30]. Thus, the interaction for the polymer bending has the form:…”
Section: Model and Simulation Detailsmentioning
confidence: 99%